Partnership Pattern Strategy between The Malaysian and Indonesian Governments in The Creative Industry Sector to Increase Exports of Creative Products through Digital Platforms - Widodo Widodo; Supriyoko Supriyoko; Azhari Md Hashim; Suparmin Suparmin; Setuju Setuju (VANOS Journal of Mechanical Engineering Education, 2024)
Industry 4.0 is a challenge for organizations , technological advances must be optimized as well as possible. Cooperation is a concept that can be done to build a stronger and more sustainable creative economy in the digital era. Strengthening creative ideas with marketing strategies and product design will increase consumer appeal such as through websites, e-commerce, social media with wide and easy reach. The purpose of this study is to develop international cooperation for branding the local creative economy through marketing strategies and creative product design. The research method uses action research, action research by developing collaboration between PVTM, Maeswara Basket and UiTM Malaysia. through the concept of marketing strategy including digital marketing, product design and catalog by collecting observation data, interviews and documentation and data analysis through collection, reduction and drawing conclusions. The results of the study describe international cooperation as an effort to improve strong marketing strategies through technology and the concept of local green economy through environmentally friendly products and more modern product design concepts and international branding are expected to provide appeal to consumers.